2008
DOI: 10.1007/s00383-008-2312-8
|View full text |Cite
|
Sign up to set email alerts
|

Is tubularization of the mobilized urethral plate a better alternative to tubularization of an incised urethral plate for hypospadias repair?

Abstract: Though the authors have an initial limited experience with this procedure, the procedure is likely to have a promising future due to its versatility and utilization of the entire urethral tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Another mechanism by which complications occur after the TIP procedure is the tendency for contraction and shrinkage of the two raw area surfaces after the dorsal midline incision in the process of healing [16][17][18] . As a result, the width of the dorsal incision decreases after complete epithelialization, which is why a narrow urethral plate is associated with urethral stenosis after the TIP procedure [19,20] . Similarly, these kinds of contraction and shrinkage increased the tension on the ventral suture line during primary healing, and postoperative urethral stulas are more likely to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism by which complications occur after the TIP procedure is the tendency for contraction and shrinkage of the two raw area surfaces after the dorsal midline incision in the process of healing [16][17][18] . As a result, the width of the dorsal incision decreases after complete epithelialization, which is why a narrow urethral plate is associated with urethral stenosis after the TIP procedure [19,20] . Similarly, these kinds of contraction and shrinkage increased the tension on the ventral suture line during primary healing, and postoperative urethral stulas are more likely to occur.…”
Section: Discussionmentioning
confidence: 99%
“…On application of stepwise binary logistic regression, Ratan et al . [ 7 ] showed that unfavorable local anatomical factors and urine leakage are strong risk factors for urethrocutaneous fistula. They showed local infection as the moderate risk factor for the development of urethrocutaneous fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the two raw surfaces of the dorsal midline incision of the urethral plate usually have a natural tendency to contract and shrink – not scar contracture – to re-approximate to each other minimising the raw area needs epithelial creeping and covering [19] , [20] , [21] , [22] . Thus, the width of the dorsal incision of the urethral plate decreases after complete healing, which can result in neourethral and/or meatal stenosis [20] , [23] , [24] . Thus, the healing of the TIP neourethra is unpredictable; it seems that this process may exert tension on the ventral suture line affecting its primary healing ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the healing of the TIP neourethra is unpredictable; it seems that this process may exert tension on the ventral suture line affecting its primary healing ( Fig. 3 ) [20] , [21] , [22] , [23] , [24] , [25] .…”
Section: Discussionmentioning
confidence: 99%